Magnetic Squeeze-Films - Anderson, Colin George (The University of Edinburgh, 1983)
Design proposals for a magnetic-repulsion enhanced hydrostatic bearing for the type N2 wave-power buoy
Design proposals for a magnetic-repulsion enhanced hydrostatic bearing for the type N2 wave-power buoy
Keywords: Edinburgh Wave Power Group; Point absorber; Structural loading; Materials